210k views
3 votes
If f(x) = x2 -1, what is the equation for f–1(x)?

User Freiheit
by
5.8k points

2 Answers

5 votes

Answer:

Inverse function is


f^(-1)(x)=\pm √(x+1)


Explanation:

Given that
f(x)=x^2-1

Now using that equation of f(x), we need to find equation of the inverse function


f(x)=x^2-1


f^(-1)(x)


Step 1: Replace
f^(-1)(x) with y


y=x^2-1


Step 2: Switchx and y


x=y^2-1


Step 3: Solve for y


x=y^2-1


x+1=y^2-1+1


x+1=y^2


y^2=x+1

take square root of both sides


y=\pm √(x+1)


Hence inverse function is


f^(-1)(x)=</strong>\pm <strong>√(x+1)



User Lesyk
by
6.0k points
4 votes

Answer:


f^(-1)=+-√(x+1)

Explanation:

f(x) = x^2 -1

We need to find f^-1(x)

WE find inverse of f(x)

Replace f(x) with y


y= x^2 -1

Replace x with y and y with x


x= y^2 -1

Solve for y

add 1 on both sides ,
x+1= y^2

To remove square , take square root on both sides


√(x+1) =√(y^2)


√(x+1) =y


y=+-√(x+1)

Replace y with f^-1


f^(-1)=+-√(x+1)

User Martin Brisiak
by
5.8k points